Round Trip Routing for Energy-Efficient Drone Delivery Based on a Public Transportation Network - Huang, Hailong; Savkin, Andrey V.; Huang, Chao (IEEE transactions on transportation electrification, 2020)
Focusing on using drones to deliver packages, this article considers a new delivery mode exploiting public transportation vehicles. Due to the battery capacity constraint, which limits the delivery area of drones, the public transportation vehicles are used to transport a drone to someplace unreachable by flying only. The problem under investigation is the round trip routing problem that finds the shortest path in terms of time in a time-dependent network, subject to the delivery deadline constraint and the energy budget constraint. The time-dependent network composes of the transit network and some extra drone flights. An exact solution algorithm is developed to find the optimal round trip path, and then, it is extended to accommodate the randomness of the considered network. The effectiveness is demonstrated via computer simulations.